Efisiensi Sistem Multi Soil Layering Pada Pengolahan Air Limbah Domestik Pada Daerah Perkotaan Padat Penduduk - Riyanto Haribowo; Sonia Megah; Windy Rosita (Fakultas Teknik, Universitas Brawijaya, 2019)
The discharge of domestic wastewater in urban areas without effective treatment may result in contamination of surrounding surface water. This study explored the wastewater treatment performance of multi-soil-layering (MSL) on domestic wastewater. Domestic wastewater parameter was use are Total Suspended Solids (TSS), Total Dissolved Solids (TDS), pH, Dissolved Oxygen (DO), Turbidity and Electrical conductivity (DHL). The experiment consisted of two stages, in stage 1, three partition in the reaktor was filled with layers of rock consisting of gravel, zeolite, and mix between gravel and zeolite. In stage 2, from the best results in stage 1, then added with stuffing mixture of andosol soil and coconut shell charcoal, mixture of andosol soil and sawdust and also mixture of andosol soil and rice straw charcoal. From the result it can be concluded that MSL with zeolite layer and mixture of andosol soil and coconut shell charcoal are the best result to purify the domestic wastewater. The efficiency for TSS, TDS, pH, DO, Turbidity and EC was 64.55%; 24.52%; 4.89%; 81.88%; 76.69% and 31,77% respectively.